Nutritional state of patients with lung cancer undergoing thoracotomy. Issue 3 (March 1990) - Bashir, Y; Graham, T R; Torrance, A; Gibson, G J; Corris, P A
Abstract : Preoperative nutritional assessment was carried out on 39 consecutive patients with bronchial carcinoma who underwent thoracotomy. For 18 patients the body mass index and triceps and subscapular skinfold thickness fell below the 25th centile. In 23 patients the creatinine height index was less than 80% of the predicted value. The mean (SEM) serum albumin concentration was 40.3 (0.57) g/l (reference range 35-50 g/l) and mean (SEM) serum transferrin 1.77 (0.1) g/l (reference range 2.0-3.0 g/l). Although only three patients were hypoalbuminaemic, transferrin concentrations were depressed in 26 patients. There was a significant fall in the serum concentrations of both prealbumin and transferrin in the first postoperative week. Nutritional insufficiency was particularly severe in the four patients who developed an early bronchopleural fistula. It is concluded that protein-energy malnutrition is common in patients with operable bronchial carcinoma and that routine postoperative feeding does not prevent further depletion of circulating proteins. A larger prospective study is needed to examine the relation between preoperative nutritional state and outcome.